CONCEPTUAL REVIEW OF MICROFINANCE AND WOMEN HOUSEHOLD, ECONOMIC, AND SOCIAL EMPOWERMENT OF MICROFINNACE BORROWERS - Haque, Tasnuba; Siwar, Chamhuri; Bhuiyan, Abul Bashar (Asian Finance & Banking Review, 2022)
The poor women are ignored in most parts of the society, having no opportunities for self-sufficiency, losing of their self-confidence and self-supporting; in turn, leads to suffer of their psychological, social, and mental health problems. Therefore, the study aims to investigate rigorous review of literature on the women empowerment for developing of a conceptual framework of microfinance and women household, economic, and social empowerment of the microfinance borrowers in the world. The present study used existing available materials and resources from reputed online data based such as google scholar, science direct, Scopus, web of science data based etc. The present study findings revealed that the poor women are marginalized, lack chances for self-sufficiency, and depend on charity or welfare. Without means to support themselves, poor women lose their self-confidence, and this disposition can lead to psychological, social, and mental problems. The study also found that the women can be empowered through encouraging and developing skills for self-sufficiency. The study also revealed that the major problems facing the poor and the lower-income group was access to credit. Their lack of assets for collateral and financial records, and limited credit history make obtaining credit from formal financial institutions almost impossible. The concluded that the Microfinance can be a powerful and effective way of access to credit of the poor has been rapidly expanding in hopeless and helpless societies accordingly. Finally, the present study developed a conceptual framework based above summary of findings to do a practical investigation to further examine the relationship between microfinance and women household, economic, and social empowerment of the microfinance borrowers in the world. JEL Classification Codes: F65.